Perspectives for Titanium-Derived Fillers Usage on Denture Base Composite Construction: A Review Article - Nidal W. Elshereksi; Mariyam J. Ghazali; Andanastuti Muchtar; Che H. Azhari (Advances in Materials Science and Engineering)
Poly(methyl methacrylate) (PMMA) is an extensively used material in dentistry because of its aesthetics, processability, and reparability. However, PMMA is still far from being ideal in fulfilling the mechanical requirements of prosthesis. PMMA-based denture base polymers exhibit low fracture resistance and radiopacity behavior. Efforts to improve the mechanical and radiopacity properties of denture base materials through inclusion of silica-based fillers are ongoing. Although silane-treated siliceous fillers are commonly used, they are not sufficiently strong. They also exhibit cracks, which either cut through the glass fillers or propagate around the filler particles. This defect occurs when the dental composites are placed in aqueous oral environment because of the hydrolytic degradation of silica-based fillers and silane-coupling agents. The clinical problem of using silanes in adhesion promotion is bond degradation over time in oral environment. In addition, silanes do not bond effectively to nonsilica-based dental restorative materials. This review presents titanium-derived fillers as alternatives to siliceous fillers. Titanate-coupling agents are found to be effective couplers in treating Ti-based fillers because of their chemical compatibility and relatively high stability in aqueous environment.